Anxiety and Depressive Symptoms Are Not Associated With Future Pediatric Crohn's Disease Activity. Issue 5 (10th July 2021) - Brenner, Erica J; Long, Millie D; Mann, Courtney M; Lin, Li; Chen, Wenli; Reyes, Camila; Bahnson, Kirsten M; Reeve, Bryce B; Kappelman, Michael D
Abstract: Background: Studies of adults with Crohn's disease (CD) suggest that poor mental health precedes worsening disease activity. We evaluated whether depression and/or anxiety forecast worsening pediatric CD disease activity. Methods: Through the Inflammatory Bowel Disease Partners Kids & Teens internet-based cohort, children with CD age 9 to 17 completed Patient-Reported Outcomes Measurement Information System (PROMIS) Pediatric measures and the short Crohn's disease activity index (sCDAI). Using general linear models, we examined how baseline PROMIS Pediatric anxiety and depressive symptom scores independently associate with subsequent sCDAI scores (average survey interval 6.4 months). Models included baseline PROMIS Pediatric anxiety and depressive symptoms scores, baseline sCDAI, sex, age, parental education, race/ethnicity, and prior IBD-related surgery. We performed a post hoc subanalysis of children in baseline remission (sCDAI <150) with otherwise identical models. Results: We analyzed 159 children with CD (mean age 14 years, 45% female, 84% in baseline remission). We found no association between baseline PROMIS Pediatric anxiety score and subsequent sCDAI (change in sCDAI for 3-point change in PROMIS Pediatric −0.89; 95% CI −4.81 to 3.03). Baseline PROMIS Pediatric depressive symptoms score was not associated with future sCDAI (change in sCDAI for 3-point change in PROMIS Pediatric <0.01; 95% CI −4.54 to 4.53). In a subanalysis of patients in remission at baseline, the lack of association remained. Conclusion: We found that neither anxiety nor depressive symptoms associate with subsequent disease activity in pediatric CD. These findings contrast with adult IBD studies, thus underschoring the unique pathophysiology, natural history, and outcomes of pediatric CD.